Targeted enrichment of nucleic acid bionic arms enhances the hydrolysis activity of nanozymes for degradation and real-time monitoring of organophosphorus pesticides in water - Zhou, Jialong; Xiong, Dinghui; Zhang, Hu; Xiao, Jiaxuan; Huang, Rui; Qiao, Ze; Yang, Zhugen; Zhang, Zhen (American Chemical Society, 2025)
Organophosphorus pesticides (OPs) pose significant environmental and health risks, and their detoxification through catalytic hydrolysis using zirconium-based metal-organic frameworks (Zr-MOFs) has attracted considerable interest due to the strong Lewis acid metal ions. Albeit important, the defects of the materials for OP hydrolysis (e.g., poor degradation efficiency, rate, and selectivity) limit their further application. Herein, a nucleic acid bionic arm-modified biomimetic nanozyme (MOF-808-Apt) was designed through a Zr-MOF and a specific aptamer against OPs, which was employed for the efficient and selective degradation of OPs. At the system, the functionalized biomimetic nanozyme can continuously capture trace OPs onto its catalytic sites for degradation with the fabricated nucleic acid bionic arms, significantly improving their catalytic activities compared to bare MOF-808 using paraoxon as a model of OPs, providing better performances including (i) an excellent degradation efficiency, boosting from 4 to over 60% within 6 min; (ii) a satisfactory catalytic rate (the pseudo-first-order rate constants of paraoxon hydrolysis improved from 0.09 to 0.14 min-1); and (iii) good selective degradation because of aptamers used. Besides, this dynamic degradation process could be visually recorded in real time with high sensitivity (limit of detection, 0.18 μM) because of the obvious color change of the reaction solution and signal amplification ascribed to increasing local concentrations of targets by the nucleic acid bionic arms. Summarily, this work provides a new strategy for the effective and selective degradation of typical OPs and concurrent monitoring of their dynamic degradation process.
Keywords: metal-organic framework; nanozyme; signal amplification; rapid detection; organophosphorus pesticides; 4105 Pollution and Contamination; 34 Chemical Sciences; Biotechnology; Environmental Sciences; Pesticides; Hydrolysis; Organophosphorus Compounds; Nucleic Acids; Water Pollutants, Chemical; Metal-Organic Frameworks; Zirconium